Analyzing the heat island magnitude and characteristics in one hundred Asian and Australian cities and regions - Santamouris, M. (The Science of the total environment, 2015)
Urban heat island is the more documented phenomenon of climate change. Information on the magnitude and the characteristics of the canopy layer urban heat island measured in 101 cities and regions of Asia and Australia and collected through 88 scientific articles, are compiled, evaluated and presented. Data are classified in several clusters according to the experimental protocol used and the type of statistical information reported regarding the magnitude of the urban heat island. Results and detailed analysis are given for each defined cluster. Very significant differences on the UHI intensity are found between the clusters and analyzed in detail. The detailed impact of the main weather parameters and conditions on the magnitude of the UHI is also investigated. The specific influence of anthropogenic thermal fluxes as well as of the urban morphological and construction characteristics to UHI is thoroughly examined. The relation between the UHI intensity and the city size is assessed and global relationships of UHI as a function of the urban population are proposed. The seasonal and diurnal variability of the UHI is analyzed and discussed while specific features and conditions like the urban heat island characteristics in coastal cities and the existence of daytime cool islands are explored. Finally, the impact of the selected reference station and its characteristics is considered.